IMPLEMENTASI KEBIJAKAN PENGENDALIAN DAN PENGAWASAN MINUMAN BERALKOHOL DI KABUPATEN KEEROM - Slamet Slamet; Akbar Silo; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2023)
This study aims to identify and analyze the implementation of Regional Regulation No. 5 of 2014 concerning the Control and Supervision of Alcoholic Beverages in Keerom Regency, and analyze the inhibiting and supporting factors for the Implementation of Regional Regulation No. 5 of 2014 concerning Control and Supervision of Alcoholic Beverages in Keerom Regency. The research method used is descriptive qualitative. Research informants were taken from SKPD officials and staff members of TP2MB, representatives of community leaders, and religious and community shops. Data collection techniques include interviews, and observation, as well as documentation. Data were analyzed using qualitative analysis of data reduction, data presentation, and conclusion drawing. The results of the study indicate that policy implementation, seen from the communication aspect, conveying information or outreach to the public about the Keerom District Alcoholic Beverage Regulation Policy as the target group of the policy has not been implemented optimally. The resource aspect, in terms of human resources, is well available. but the financial resources are not yet available properly while the infrastructure resources have not met the needs. In the aspect of disposition, the attitude of policy implementers shows commitment and firmness toward implementing alcohol regulatory policies. The aspect of the bureaucratic structure was strengthened by the issuance of Regent Regulation Number 62 of 2018 concerning the Formation of an Alcoholic Beverage Supervision and Development Team. The supporting factors are regulatory derivatives for technical issues, consistency and strong support from the community, and the commitment of policy implementers to the optimal deployment of resources. While the inhibiting factors include budget constraints, ineffective inter-agency coordination, and some people still lack awareness because the socialization has not been thorough.